Design and Implementation of Ordering and Payment Information System at Aisya Catering Surabaya - Fitri Retrialisca; Citra Ayu Wulandari; Umi Chotijah (Jurnal Tekno Kompak, 2022)
Catering is a business that focuses on catering services in Surabaya and its surroundings. So far, the ordering process has been recorded in Whatsapp messages and google form, then re-recorded in spreadsheet. Aisya Catering wants to develop the ordering process and provide convenience for potential customers and Aisya Catering itself by creating a system where orders from customers can be directly entered into the system and the status can be seen easily and neatly. The organization considers that this will make existing business processes easier and organized. Thus, this final project is proposed to build an Order and Payment Information System for Aisya Catering Surabaya, then it can be used by the organization concerned to support its business processes to be more optimal. This system handles two main processes as the title suggests: the ordering process and the payment process. There are five stages through the development of building Aisya’s system based on SDLC. Firstly, knowing the needs by interviewing stakeholders to define the existing problem. Second, analyze the existing system problem and its new requirements with the help of Document Flow Diagram (DocFlow) and Fishbone Diagram. Third, design the new system using Tier Diagram (HIPO Diagram) and Data Flow Diagram (DFD), Conceptual Data Model (CDM) produces 8 entities, Physical Data Model (PDM) generates 10 tables in total, then process with designing input and output forms. Fourth, adjust the system design workflow illustrated in flowcharts, and implement it into a web-based program using Laravel 8.14 framework. And the last stage is testing the system program. Based on the implementation and testing results, the order and payment information system for Aisya Catering Surabaya has been in accordance and met with the predefined functional requirements of the testing process.